Public pensions and labor supply over the life cycle - Eric French; John Bailey Jones (Federal Reserve Bank of Chicago, 2010)
Virtually all developed countries face projected budget shortfalls for their public pension programs. The shortfalls arise for two reasons. First, populations in developed countries are aging rapidly. Second, until recently older individuals in developed countries have been retiring earlier. These two developments have created serious strains on public pension programs. In order to remain fiscally solvent, many governments have reformed their public pension schemes to encourage labor supply at older ages. These reforms include reductions in the generosity of public pensions and reduced penalties for working past the normal retirement age. In this paper, we consider how reforms to public pension systems affect labor supply over the life cycle. We put the recent empirical evidence on the effect of government pensions on labor supply in a life cycle context, and we present evidence on the effectiveness of tax reforms for stimulating labor supply over the life cycle. Our main conclusion is that the labor supply of older workers is responsive to changes in retirement incentives. The labor supply of younger workers is less responsive. Thus the trend towards lower taxes on older workers in many developed countries is likely to continue to fuel the recent trend towards later retirement. This, in turn, is likely to reduce the financial strain on public pension schemes.
Keywords: 330